Information security of the personnel of the State Border Guard Service of Ukraine: problematic issues of normative and legal regulation - V. V. Polovnikov (Law and Safety)
The article analyses the current legislation of Ukraine which provides for normative and legal regulation of public relations in the information sphere of activity of security and defence forces, in particular, the State Border Guard Service of Ukraine, and also the scientific views of scholars on the content of the concepts of information security of an individual, society and the State.